How well the balance-of- payments constraint approach explains the Portuguese growth performance. Empirical evidence for the 1965-2008 period. - Micaela Antunes; Elias Soukiazis (European Regional Science Association (ERSA), 2010)
The present study aims to verify whether the balance-of-payments constrained growth approach is suitable for explaining the Portuguese growth performance during the last decades. For that, we adopt "Thirlwall's Law" that predicts actual growth by the ratio of the exports growth relative to the income-elasticity of the demand for imports. The income-elasticity of imports, essential for the entire analysis, is obtained from the estimation of the imports function by 2SLS, assuming that domestic growth is endogenous. To smooth cyclical variations, 15-year overlapping periods are considered in the computation of "Thirlwall's Law", assuming that income-elasticity with respect to imports is either constant or variable over time. It is found that the Law is a good instrument for predicting actual growth in Portugal and this result is reinforced by performing the McCombie test. Our results reveal that Portugal grew slightly higher relatively to the OECD countries in the entire period and this is consistent with the income-elasticity of the demand for exports exceeding that of imports, as "Thirlwall's Law" implies. Portugal also grew slightly faster than the rate consistent with the balance-of-payments equilibrium, accumulating external deficits over time. Dividing the sample in the pre and post-adhesion period to the EU, it is shown that Portugal grew at a lower rate in the latter, and this is consistent with lower export growth and higher income-elasticity with respect to imports. To overcome this problem, policies are needed to improve the supply characteristics of exports related to non-price competitiveness and reduce the imports sensitivity with respect to domestic income changes.
Keywords: C13; E12; F43; O24; 330; balance-of-payments equilibrium growth rate; income-elasticities with respect to trade; overlapping periods; 2SLS regressions